ORGANIZATION OF THE MANAGEMENT AT MATERIAL AND TECHNICAL SUPPLY OF THE SUBJECTS AT LOGISTICS ACTIVITIES: SECURITY KNOWLEDGE CONTEXTS - SHATARSKYI, Artur (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the concept of logistics, as well substantiates the material and technical support of subjects the logistics activity. On the basis of which, a practical safety mechanism for the subjects of logistics activity is presented. A comprehensive study the methodology of forming a system for ensuring the safety of logistics activity subjects was conducted. The main factors for improving the use of material resources have been identified. The components of the economic effect from the application of  logistics approach to management of material flows of subjects the logistics activity are substantiated.Ensuring the implementation of the process of creating products requires the presence of a specialized structural unit in the organizational structure of the subject of logistics activity, which must coordinate the process of material and technical supply of production and develop and implement measures to reduce the cost of material resources. We will determine the following components of the economic effect from the application of the logistics approach to the management of material flows of the subjects of logistics activity: partnership relations with suppliers are established; reduced idle equipment. This is ensured by the fact that materials for work are constantly needed at workplaces; Optimizing stocks is one of the central problems of logistics. Maintaining stocks requires the diversion of financial resources, the use of a significant part of the material and technical base, labor resources; the number of auxiliary workers is reduced; the quality of the produced products improves; material losses are reduced. Since any logistics operation is a potential loss, and the optimization of logistics operations is a reduction of losses; the use of production and warehouse space improves. The approaches to the logistics of material flows of logistics entities considered in the work can be used in further scientific research related to the optimization of logistics systems.
Keywords: logistics; security; security system; subjects of logistics activity; management of subjects at logistics activity; material and technical support